Types of Polish Agrotourism Farm and Owner Profiles - Wojciechowska, Jolanta (Turyzm/Tourism, 2007)
The author presents a classification of agrotourism farms in the light of ‘objective’, ‘subjective' and 'relative' criteria. Agro-tourism farms of the ‘objective-subjective’ ‘genotype’ are considered predominant in Poland. Six different profiles of agro-tourism farm owner are distinguished.